Asymmetric information issues in micro-business financing of Baitul Maal wa Tamwil - Martiana, Andri; Kassim, Salina; Zakariyah, Habeebullah (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – Despite its potential advantages, poverty interferes with economic progress in developing countries, obstructing small and medium-sized businesses from obtaining external financial assistance via Islamic microfinance. This study explores the problems related to asymmetric information in the context of funding microbusinesses in Baitul Maal wa Tamwil (BMT), with the goal of improving our understanding of the risks associated with financing in Islamic microfinance institutions, namely BMTs.Methodology – This research utilized a qualitative approach and content analysis to study BMTs in Indonesia, involving academics, practitioners, and voluntary participants. The sample size was adequate for achieving data saturation.Finding – This study demonstrates that there might be asymmetric information during the execution of contracts, leading to deviant behavior by BMT management and partners. The study additionally identified the risk characteristics present in Islamic MFIs, emphasizing the necessity for implementing novel lending mechanisms, such as group lending and individual collateralized loans. Implication – This study underscores the importance of resolving the substantial administrative overheads associated with these institutions. It is advisable to utilize additional research methods such as interviews, observations, and documentation to augment the depth of the research and engage a varied array of individuals for a comprehensive collection of information.Originality – Studies of Islamic microfinance in Indonesia have examined its performance, obstacles, and experience. However, empirical data on agency problems such as moral hazard and asymmetric knowledge are lacking. For optimal BMT operating efficiency and Shariah compliance, it is essential to comprehend these challenges.